THE STUDY OF THE EXPECTATIONS FOR FOREIGN LANGUAGE LEARNING MANAGEMENT TO BUILD GRADUATES 4.0 - โกมารทัต, สมพร (CRMA Journal of Humanities and Social Sciences, 2021)
This quantitative research is aimed at studying the expectations of foreign language learning management in the training of graduates for the digital age (or Graduates 4.0, according to the Thailand 4.0 National Strategy) and to compare expectations regarding the management of foreign language learning from the perspectives of learners and instructors. The population and samples were learners and instructors at the undergraduate level from universities in Bangkok and its vicinity. The questionnaire was the main research tool. Statistical tools used for data analysis were percentages, mean scores, standard deviation, and the Independent–sample t-test analysis. The research results showed that: 1) Learners and instructors had consistent opinions on the expectations and goals of foreign language learning for the digital age, focusing on individual skills in communications, listening, speaking, reading and writing (Interpersonal Communication), to interpret and analyze what is perceived and communicated (Interpretive Communication), and to present information and communicate ideas (Presentation Communication). This graduates’ foreign language program is a course that integrates knowledge and language, with an emphasis on language competencies and the utilization of blended learning as the main principle of learning management; and 2) The expectations for foreign language learning management from the perspective of the learners and instructors did not differ.